Preferable Orientations of Interacting C60 Molecules inside Single Wall Boron Nitride Nanotubes*Supported by the National Basic Research Program of China under Grant No 2011CB808200, the National Natural Science Foundation of China under Grant Nos 11504150, 11304020 and 51320105007, and the Cheung Kong Scholars Programme of China. (May 2016) - Yao 姚, Zhen 震; Lv 吕, Jia-Yin 佳音; Liu 刘, Chun-Jian 春见; Lv 吕, Hang 航; Liu 刘, Bing-Bing 冰冰
Abstract : This work focuses on the preferable orientation analysis of the hybrid system where the C60 molecules are encapsulated inside the boron nitride nanotubes by using the two-molecule model. The low-energy state can be acquired in the contour map, which provides the visual information of the systematical van der Waals interaction potential for the C60 molecules adopting different orientations. Our results show that the C60 molecules exhibit the preferred pentagon and hexagon orientations with the tube's diameter smaller and larger than 13.55 Å, respectively. The preferred two-bond orientation obtained in the single-molecule model is absent in this study, indicating that the intermolecular interaction of adjacent C60 molecules plays an important role in the orientational behaviors of this peapod structure.